Exploring the relationship between mental health issues and academic performance of undergraduate students in a Ghanaian tertiary institution: a cross-sectional study - Andrew Nketsia Arthur; Joanne Fraikue; Bijoux Adu-Amankwah; Richard Ofori; Dorcas Sekyi; Abena Afrakomah Boateng; Elsie Asamoah; Seth Christopher Yaw Appiah (Discover Mental Health)
Abstract Background Mental health associations with students’ academic outcomes are critical for students’ well-being and excellent performance, particularly among tertiary students in their educational trajectory. This study investigated the relationship between mental health incidence and academic performance among university students in a public university in Ghana. Additionally, we study students’ level of mental health awareness. Methods The study adopted a quantitative study with an analytical cross-sectional design. Through the multistage sampling technique, structured questionnaires were administered to 384 undergraduate students at Kwame Nkrumah University of Science and Technology (KNUST). Data management and analysis were performed using SPSS v.27. Descriptive data are presented in tables and reported as frequencies. Inferential analysis was conducted using a multilevel logistic regression model and a p-value of 0.05 was considered to indicate statistical significance. Results Severe depression (p = 0.016, ϰ2 = 0.784) was significantly associated with students’ academic performance. Severe anxiety (p = 0.020, ϰ2 = 11.700), gender (p = 0.014, ϰ2 = 5.999) and self-efficacy (p = 0.015, ϰ2 = 5.939), were found to have a statistically significant association with academic performance (p < 0.05). According the multilevel analysis, females experiencing mental health had reduced likelihood of achieving high academic performance compared to male students (AOR = 0.343, 95% CI 0.144–0.813, p = 0.015). Severely depressed students (AOR = 0.264, 95% CI 0.084-0.830, p = 0.23) are significantly less likely to increase their Cumulative Weighted Average (CWA). Self-efficacious students (AOR = 3.325, 95% CI 1.421-7.784, p = 0.06) were three times more likely to increase their CWA. Conclusion Severe depression causes a reduction in students’ academic performance, while high academic self-efficacy among students serves as a protective factor by facilitating an increase in students’ CWA when they encounter mental health issues.